2016
DOI: 10.1515/botcro-2016-0030
|View full text |Cite
|
Sign up to set email alerts
|

An Eco-physiological and Biotechnological Approach to Conservation of the World-wide Rare and Endangered Aquatic Liverwort Riella helicophylla (Bory et Mont.) Mont.

Abstract: -The rare aquatic liverwort Riella helicophylla (Bory et Mont.) Mont., inhabitant of temporary shallow ponds around the Mediterranean basin, is considered threatened throughout its distribution range. In addition, little is known of its biology and ecology or of its role in such an important ecosystem where environmental conditions vary yearly in unpredictable ways. In these variable habitats, due to the seasonal fl uctuation of water levels, there is no guarantee of yearly spore input into the spore bank. Spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…However, sampling of soil sediments at promising sites for later laboratory cultures has proven a successful strategy Segarra-Moragues et al 2019a). Recent progress in laboratory culture and the required physico-chemical conditions of spore germination provides unique opportunity to discover the species occurrence by cultivating the sediments taken from potentially suitable areas (Sabovljević et al 2016). The combination of the two methods can thus, increase the possibilities to discover both new populations and species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, sampling of soil sediments at promising sites for later laboratory cultures has proven a successful strategy Segarra-Moragues et al 2019a). Recent progress in laboratory culture and the required physico-chemical conditions of spore germination provides unique opportunity to discover the species occurrence by cultivating the sediments taken from potentially suitable areas (Sabovljević et al 2016). The combination of the two methods can thus, increase the possibilities to discover both new populations and species.…”
Section: Discussionmentioning
confidence: 99%
“…The family Riellaceae (Marchantiophyta, Sphaerocarpales) consists of two genera, the monotypic Austroriella, known only from a single locality in Australia (Cargill and Milne 2013) and Riella, with a world-wide distribution (except Antarctica) and 29 taxa (Söderström et al 2016, Table 1). The majority of the Riella populations are found in areas of Mediterranean-type and subtropical semi-arid climates with a marked precipitation seasonality and develop in seasonally flooded shallow lake and wetland environments (Gradstein 2016;Sabovljević et al 2016). Riella species have very small and disjunct populations mostly distributed in the Mediterranean bioclimatic areas of the world (e.g.…”
Section: Model Taxon: Riellamentioning
confidence: 99%
“…Mont. Sabovljević et al [ 41 ] developed bi-phase axenic in vitro systems, a solid one for spore germination and a liquid form for gametophore development. When combined, the solid form containing minerals and essential salts, and the water cover was not enough to achieve vigorous development.…”
Section: Some Examples Of Incidental and Intentional Bryophyte Conser...mentioning
confidence: 99%
“…When combined, the solid form containing minerals and essential salts, and the water cover was not enough to achieve vigorous development. The imitation of brackish water conditions, i.e., establishing the liquid electrolytic solution over the solid medium cover, induced the vigorous development of gametophores well anchored in the solid medium [ 41 ]. The same authors reported spore dormancy and breaking dormancy to be unsuccessful when applying gibberellins conventionally as for breaking seed dormancy.…”
Section: Some Examples Of Incidental and Intentional Bryophyte Conser...mentioning
confidence: 99%
“…Apart from its high conservation value, Riella helicophylla has long been used as a model organism in plant physiology research. This includes topics such as the effects of plant regulators in cellular differentiation and morphogenesis (Stange, 1977, 1984, 1992; Viell, 1980a,b; Witt, 1992; Sabovljević & al., 2016), plant cell cytokinesis (Grotha, 1983, 1986; Lerchl & al., 1989; Oliev, 1994; Sherp & al., 2001, 2002, 2004), synthesis of nucleic acids (Bentler, 1989; Eisenbeiser‐Engelbrecht, 1986; Heupel & Stange, 1995), thallus regeneration (Lehmann, 1966; Viell, 1980b; Lehmann & Herzmann, 1989), plant volatile compounds (Becker & Martini, 1999), oil body function (Lehmann & Jaster, 1981) and photosynthesis (Conde‐Álvarez & al., 2002). This may be in part due to the simple gametophyte structure (most of the thallus is composed of a single‐cell layered wing), the rapid growth of the plants and ease of multiplication, and little demands for cultivation in the laboratory (Viell, 1983).…”
Section: Introductionmentioning
confidence: 99%